(untitled) (LACCEI, 2024)
The objective of the research was to analyze the compressive and flexural strength of adobe blocks compacted with 0.5%, 0.75% and 1% bamboo sheath of 4 cm, 5 cm and 6 cm, with respect to the weight of the soil of the La Paccha quarry in Cajamarca. The quantitative approach study had a sample of 140 adobe blocks, 60 blocks for the compression test and 80 blocks for the flexural test, made with bamboo sheath fiber. The compressive strength of the adobes increases up to 82.49% for adobes with 0.75% of 5 cm bamboo fibers, with respect to the UNE 41410 standard [15], while the standard adobes only reach 8.47 kg/cm2, therefore, they do not even comply with the E.080 standard likewise, for adobes with 0.5% of 5 cm bamboo fibers, in bending, they exceed up to 71.44% of the standard adobes with 15.51 kg/cm2. It is concluded that the bamboo fiber increases the mechanical capacity of the compacted adobes, surpassing the hypothesis that indicated an increase of up to 25%, complying with the requirements of the E.080 standard